Ten New Species of Myrmica (Hymenoptera, Formicidae) from the Himalaya - Radchenko, A.G.; Elmes, G.W. (Вестник зоологии, 1999)
Ten new species discovered among collections examined in the course of a taxonomic revision of the Myrmica species of the Himalaya and the adjacent mountain regions of India and Pakistan are described: Myrmica brancuccii, M. villosa, M. vittata, M. williamsi, M. nitida, M. wittmeri, M. wardi, M. ordinaria, M. rhytida and M. petita. They belong to several quite different complexes of species of the genus Myrmica, but clearly differ from each other and all previously described forms. Distinctions of each species and data on their ecology are given.